Search for decays of B-0 mesons into e(+)e(-), mu(+)mu(-) and e(+/-)mu(-/+) final states - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2008)
We present a search for the decays B0→e+e-, B0→μ+μ-, and B0→e±μ using data collected with the BABAR detector at the PEP-II e+e- collider at SLAC. Using a data set corresponding to 384×106 BB̄ pairs, we do not find evidence of any of the three decay modes. We obtain upper limit on the branching fractions, at 90% confidence level, of B(B0→e+e-)<11.3×10-8, B(B0→μ+μ-)<5.2×10-8, and B(B0→e±μ)<9.2×10-8. © 2008 The American Physical Society.